The Influence Of Brand Image And Price On Decisions Purchase Of Telkomsel Simpati Cards - Mery Sabina Lingga; Neni Sri Wahyuni; Tengku Ahmad Helmi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In this study, it has purpose , namely For analyze and know how much big influence image brand to decision purchase card Sympathy Telkomsel in the environment Students , influence price to decision purchase card Sympathy Telkomsel in the environment Students . This research was conducted at the Islamic University of North Sumatra, precisely at the Faculty of Economics and Business, Management Study Program, class of 2021. The sampling The sample in this study used simple random sampling, with total 63 respondents . This type of research is quantitative . The results of this study are : Brand image No influential positive to decision purchase card Sympathy Telkomsel to Students Faculty of Economics and Business, Islamic University of North Sumatra, Management Study Program class of 2021. Prices are affected positive to decision purchase card Sympathy Telkomsel to Students Faculty of Economics and Business, Islamic University of North Sumatra, Management Study Program class of 2021. Brand image and Price in general together can influence decision purchase card Sympathy Telkomsel to Students Faculty of Economics and Business, Islamic University of North Sumatra, Management Study Program class of 2021.